Images and meaning [videorecording] a selection for media literacy studies ([Montreal] NFBC)
An enlightening series on the role of mass communication in society. Each part combines documentary, animated and dramatic segments of media.
1. Zea 2. Street kids 3. Elephantrio 4. Nails 5. Aloud Bagatelle 6. Return to Dresden 7. Age of invention 8. Ashes of doom 9. Debts.
Keywords: Media programs (Education).; Literacy; Education; Mass communication